서울과 전라 지역 성인 화자의 생활어휘 발화 내 모음의 모음공간면적 - 심이슬(Lee Seul Shim); 이옥분(Ok Bun Lee); 한지연(Ji Yeon Han) (언어치료연구, 2010)
이 연구에서는 서울과 전라 지역 정상 성인화자들이 발화한 일상어휘에서 선택한 모음들을 음향학적으로 분석하여 모음공간에 대한 특성을 알아보았다. 모음공간은 말명료도와 밀접한 음향학적 측정치의 하나로 보고되고 있는데, 말명료도 문제가 있는 의사소통장애에서 비교자료의 필요성을 고려해볼 때 정상화자에 대한 선행연구가 요구된다. 이 연구에서는 8명의 남성 화자와 여성화자(20대-30대)가 참여하였으며, 일상생활에서 친숙하게 사용되는 어휘들을 샘플링하여 그 중 540개의 모음을 샘플링하였다. 모음공간을 산출하기 위해 샘플링 된 토큰에서 /이/, /애/, /우/, /아/에 선택하여 분석하였다. 그 결과 남성 집단 내에서 전라 지역이 서울 지역에 비해 모음공간면적이 유의하게 넓게 나타났으며, 여성 집단 내에서도 동일한 결과가 산출되었다. 남성 집단에서 모음공간면적의 차이에 영향을 미친 모음은 /이/와 /애/였고, 여성 집단에서는 /우/, /애/, /아/였다. 연구 결과를 토대로 추후 연구에서는 모음도 산출의 방법적 측면과 대상자 표집특성에 따른 차이를 고려하여 계속 연구되어야 할 것이다. The purpose of this study was to examine the characteristic of vowel space for spoken words by Korean adult speakers. Vowel space has been reported to be one of the sensitive acoustic measures related with speech intelligibility. Basically, for more effective application of vowel space in clinical viewpoint, it is natural to study the vowel space for Korean adults with normal speech. Eight male and eight female speakers (aged from 20 to 30) participated in this study. 540 tokens in familiar and daily-life words were used for speech sampling. Corner vowels, /i/, /u/, /ae/, and /a/ for corner vowels were used for the calculation of vowel space. Between single subjects, a t-test was performed for identifying the differences of vowel space between male and female speakers, between two dialects of Korean. The results showed that there was a significant difference between two dialects of male and female speakers. In addition, Jeolla-dialect speakers showed significantly wider vowel space than Seoul dialect speakers. In addition, the value of vowel space area in female speakers was higher than male speakers. Finally, except vowel /a/, F1 and F2 value of 3 vowels (i, u, ae) affected vowel space area. Normalization and clinical implications of these results will be discussed. KCI Citation Count: 4